Comprehensive Analysis of SMC Gene Family Prognostic Value and Immune Infiltration in Patients With Pancreatic Adenocarcinoma - Nie, Hui; Wu, Yanhao; Ou, Chunlin; He, Xiaoyun (Frontiers in Medicine, 2022)
Pancreatic adenocarcinoma (PAAD) is a malignant tumor with high morbidity and mortality worldwide. The structural maintenance of chromosomes (SMC) family of genes and non-histone proteins (SMC family) is important in chromosomes.The SMC gene family functions as oncogenes in some tumor types, but its role in PAAD has not been elucidated. We explored the role of the SMC family in tumor progression and cancer immune infiltration in PAAD using integrative bioinformatics analyses. The results showed that the SMC 1A, 2, 3, 4, and 6 were overexpressed in PAAD tissues, and that SMC 1A, 4, 5, and 6 could be potential prognostic biomarkers for the survival of patients with PAAD. The expression of SMC genes was significantly associated with immune cell infiltration. According to the infiltrative status of various immune cells, the mRNA expression of SMC genes in PAAD was associated with the overall and recurrence-free survival of patients. We concluded that the SMC family is associated with PAAD and might be involved in tumorigenesis and cancer-immune interactions, and thus, these proteins could serve as promising prognostic and therapeutic biomarkers of PAAD.